Corrosion Resistance of Biodegradable Zinc Surfaces Enhanced by UV-Grafted Polydimethylsiloxane Coating - Pupillo, Davide; Bruns, Mark; Prado, Lucia; Di Franco, Francesco; Böhringer, David; Mazare, Anca Valentina; Goldmann, Wolfgang; Virtanen, Sannakaisa; Santamaria, Monica; Tesler, Alexander (ACS Biomaterials Science and Engineering, 2024)
Improved living conditions have led to an increase in life expectancy worldwide. However, as people age, the risk of vascular disease tends to increase due to the accumulation and buildup of plaque in arteries. Vascular stents are used to keep blood vessels open. Biodegradable stents are designed to provide a temporary support vessel that gradually degrades and is absorbed by the body, leaving behind healed blood vessels. However, biodegradable metals can suffer from reduced mechanical strength and/or inflammatory response, both of which can affect the rate of corrosion. Therefore, it is essential to achieve a controlled and predictable degradation rate. Here, we demonstrate that the corrosion resistance of biodegradable Zn surfaces is improved by electroless deposition of zinc hydroxystannate followed by UV-grafting with silicone oil (PDMS). Potentiodynamic polarization, electrochemical impedance spectroscopy, respiratory kinetic measurements, and long-term immersion in three simulated body fluids were applied. Although zinc hydroxystannate improves the corrosion resistance of Zn to some extent, it introduces a high surface area with hydroxyl units used to UV-graft PDMS molecules. Our results demonstrate that hydrophobic PDMS causes a 3-fold reduction in corrosion of Zn-based materials in biological environments and reduces cytotoxicity through the uncontrolled release of Zn ions.
CRIS-Team Scopus Importer:2024-07-26
Keywords: biodegradable metals; corrosion resistance; polydimethylsiloxane; UV-grafting; zinc